MENINGKATKAN KEMAHIRAN DAN PENGUASAAN TOPIK HIDROPONIK MURID DARJAH ENAM DENGAN TEKNIK DIY - Lee, M.F; Goh, W.K.; Tan, K.H. (Online Journal for TVET Practitioners, 2018)
Hydroponics is one of the sub-topics in the subject of Design and Technology in primary schools. However, most of the schools and students do not focus on this subject even though hydroponics are a global issue in addressing food supply problems. As a result, this study was conducted to improve the skills of the Hydroponics topic through Do It Yourself (DIY) technique among standard six students as well as to develop students’ interest in this topic. The design of this study is an action research and the respondents of this study consist of nine standard six students from a Sekolah Jenis Kebangsaan Cina in Johor. DIY techniques have been applied in during the learning of Hydroponics topics for the implementation of green concept to students through the use of recyclable items. Data was collected through pre-test, post-test and observation. The frequency, percentage, mean and standard deviation were used to analyze the collected data. The findings implied that students tend to have a positive improvement in theoretical and practical achievement of the Hydroponic topic. In addition, students were also become more interested in the Design and Technology subject after the DIY techniques were exposed to them. In conclusion, DIY techniques should be expanded to be use in learning and teaching for Design and Technology subject and other subjects in order to enhance the mastery of theoretical, practical and interest of students.